Antigenicity, immunogenicity and protective efficacy of a conserved Leishmania hypothetical protein against visceral leishmaniasis. Issue 6 (8th November 2017) - Dias, Daniel S.; Martins, Vívian T.; Ribeiro, Patrícia A. F.; Ramos, Fernanda F.; Lage, Daniela P.; Tavares, Grasiele S. V.; Mendonça, Débora V. C.; Chávez-Fumagalli, Miguel A.; Oliveira, Jamil S.; Silva, Eduardo S.; Gomes, Dawidson A.; Rodrigues, Michele A.; et al.
Abstract: In this study, a Leishmania hypothetical protein, LiHyS, was evaluated regarding its antigenicity, immunogenicity and protective efficacy against visceral leishmaniasis (VL). Regarding antigenicity, immunoblottings and an enzyme-linked immunosorbent assay using human and canine sera showed high sensitivity and specificity values for the recombinant protein (rLiHyS) in the diagnosis of VL. When evaluating the immunogenicity of LiHyS, which is possibly located in the parasite's flagellar pocket, proliferative assays using peripheral blood mononuclear cells from healthy subjects or VL patients showed a high proliferative index in both individuals, when compared to the results obtained using rA2 or unstimulated cultures. Later, rLiHyS/saponin was inoculated in BALB/c mice, which were then challenged with Leishmania infantum promastigotes. The vaccine induced an interferon- γ, interleukin (IL)-12 and granulocyte-macrophage colony-stimulating factor production, which was maintained after infection and which was associated with high nitrite and IgG2a antibody levels, as well as low IL-4 and IL-10 production. Significant reductions in the parasite load in liver, spleen, bone marrow and draining lymph nodes were found in these animals. In this context, the present study shows that the rLiHyS has the capacity to be evaluated as a diagnostic marker or vaccine candidate against VL.